The Assessment of Cognitive Reserve: A Systematic Review of the Most Used Quantitative Measurement Methods of Cognitive Reserve for Aging - Nogueira, Joana; Gerardo, Bianca; Santana, Isabel; Simões, Mário R.; Freitas, Sandra (Frontiers in Psychology, 2022)
The Cognitive Reserve (CR) is widely accepted as the active ability to cope with brain damage, using pre-existing cognitive and compensatory processes. The common CR proxies used are the number of formal years of education, intelligence quotient (IQ) or premorbid functioning, occupation attainment and participation in leisure activities. More recently it has employed the level of literacy and engagement in high level cognitive demand of professional activities. The present study aims to identify and summarize published methodologies to assess the CR quantitatively. We searched for published studies on PubMed, ScienceDirect and Web of Science between September 2018 and September 2021. We only included those studies that characterized the CR assessment methodology. The search strategy identified 1285 publications, of which 25 were included. Most of the instruments targeted proxies individually. The lack of a gold standard tool incorporating all proxies and cognitive tests, highlights the need to develop a more holistic battery for the quantitative assessment of CR. Further studies should focus on a quantitative methodology that includes all these proxies supported by normative data, in order to improve the use of CR as a valid measure in clinical contexts.